PENGELOLAAN SAMPAH RUMAH TANGGA DAN STOP BABS DI DESA WILAYAH KABUPATEN LEBAK BANTEN - Rusmana Rusmana; Yeyen Maryani; M. Iman Santoso (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Knowledge and skills in managing household waste and understanding the importance of stopping defecation must be mastered by the community, therefore improving skills to manage waste can be utilized and benefited as well as environmental hygiene and health through improving public health at large. The implementation method is carried out by workshops and conveying ideas through outreach activities and demonstrations to the community with household waste management using the concept of Sort-Collect-Benefit-Profit to reduce the volume of household waste and benefit the community, as well as triggering strategies which are a way to reduce household waste. volume of household waste and benefit the community, as well as triggering strategies which are ways to change individual hygiene and sanitation or community behavior on their own awareness by touching the feelings, mindset, behavior, and habits of individuals or communities, namely by providing health education to the community. This community service activity was carried out at the Bumi Katineung Rangkasbitung Hotel on September 3, 2021 with 30 participants involved in this activity consisting of representatives from 28 sub-districts in Lebak Regency, Banten Province. The achievement targets in this activity are increasing the ability of residents to manage household waste, the use of household waste for media, the importance of managing a waste bank, and the habit of stopping plant defecation. The results of this activity show that community members are very enthusiastic and have the potential to use household waste to make compost or recycle waste, and understand the importance of stopping defecation, simply. The follow-up of this activity is the formation of waste bank managers in various regions/villages and continuous counseling on the habit of stopping defecation by providing/constructing public or family latrines.